Hubungan Aliran Komunikasi Organisasi dan Gaya Komunikasi Kepemimpinan dengan Kinerja Karyawan PT Maybank Indonesia Cabang Medan - Vella Stephanie; Riris Loisa (Prologia, 2022)
This study aims to determine the relationship between organizational communication flow and leadership communication styles on the performance of employees of Bank Maybank Medan Branch. This study uses a quantitative research approach with a survey method. The population in this study were all employees of Bank Maybank Medan Branch while the sample was the entire population of 50 employees of Bank Maybank Medan Branch. The variables in this study consisted of independent variables and dependent variables. The independent variable in this study is the flow of organizational communication and leadership communication styles, while the dependent variable is employee performance. The data used in this study are primary data collected using a questionnaire. The data validity technique was done by testing the validity and reliability. The data analysis method used in this study is the Pearson product moment correlation analysis to see the relationship between the measured variables and to show the direction of the relationship between the dependent variable and the independent variable. The results of this study indicate that the flow of organizational communication has a positive relationship with the performance of employees of Bank Maybank Medan Branch and leadership communication styles have a positive relationship with the performance of employees of Bank Maybank Medan Branch.Penelitian ini bertujuan untuk mengetahui hubungan aliran komunikasi organisasi dan gaya komunikasi kepemimpinan terhadap kinerja karyawan Bank Maybank Cabang Medan. Penelitian ini menggunakan pendekatan penelitian kuantitatif dengan metode survei. Populasi dalam penelitian ini adalah seluruh karyawan Bank Maybank Cabang Medan sedangkan sampel merupakan seluruh dari populasi sebanyak 50 karyawan Bank Maybank Cabang Medan. Variabel dalam penelitian ini terdiri dari variabel independen dan variabel dependen. Variabel independen dalam penelitian ini adalah aliran komunikasi organisasi dan gaya komunikasi kepemimpinan sedangkan variabel dependen adalah kinerja karyawan. Data yang digunakan dalam penelitian ini adalah data primer yang dikumpulkan menggunakan kuesioner. Teknik keabsahan data dilakukan dengan uji validitas dan reliabilitas. Metode analisis data yang digunakan dalam penelitian ini adalah analisis korelasi pearson product moment untuk melihat hubungan antar variabel yang diukur serta menunjukkan arah hubungan antara variabel dependen dengan variabel independen. Hasil dari penelitian ini menunjukan bahwa aliran komunikasi organisasi memiliki hubungan positif dengan kinerja karyawan Bank Maybank Cabang Medan dan gaya komunikasi kepemimpinan memiliki hubungan positif dengan kinerja karyawan Bank Maybank Cabang Medan.